Analysis of human navigation and force exertion in picking and placing task for robot learning from demonstration - Wu, Tong (Nanyang Technological University, 2023)
This project introduces an experiment protocol for human operators to obtain trajectory and force data to assist the teaching of robot task planning and analyses the way humans navigate to a workpiece and exert forces to pick, move, orient, and place the object in sample experiments. The experiment is designed in 2D settings for human operators to simulate robotic picking and placing task with a pair of force-sensorized grippers, where grippers and workpieces are located by AprilTags, in both dynamic and quasi-static state, and plot out force and trajectory data collected for result analysis. Two sample runs of experiment for both dynamic and quasi-static state are conducted, and the resulted plots are compared in parallel. From sample experiment run, the trajectory and forces throughout the experiment run could be clearly observed, showing the feasibility and potentials of the protocol to be further improved and developed.